EFFECTIVE WAYS OF SOLVING THE PROBLEM OF MULTUDRUG-RESISTANT TUBERCULOSIS IN THE REPUBLIC OF BELARUS - E. M. Skryagina; G. L. Gurevich; A. P. Astrovko; O. M. Kalechits; O. M. Zalutskaya; A. E. Skryagin (Туберкулез и болезни лёгких)
The article describes the current epidemiological situation of multidrug resistant tuberculosis (MDR TB) in the Republic of Belarus and offers the new approaches to the diagnostics and treatment of MDR TB based on the experience of the Republican TB program and the recommendations of leading international experts. Implementation of new approaches will allow reducing the time necessary for diagnostics and treatment of MDR-TB and to increase its efficiency.